Improving Customer Satisfaction in Circle-K Companies Through Services in Indonesia - Arif Rahman; Fajri Ariandi; Jaka Santosa; Roynaldi Arista (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study aims to determine the influence of service to customers satisfaction at PT Circelka Utama Jakarta main Outlets Circle K Regatta Apartement Jakarta.The research method used is descriptive quantitative method. The author used SPSS Version 21 to calculate the validity test, reliability test, correlation coefficient test, test coefficient of determination, and test the regression equation. The service applied has been running well based on the result of calculation of correlation coefficient of 0.689 with error 5% table 0.689>0.20, then there is a strong correlation. Based on the coefficient of determination obtained result 0.474 or 47% value of the amount of customer satisfaction by service data, while the remaining 53% was influenced by other factors such as price, promotion, and corporate image. Based on the research showed the quality service which includes the tangible, realibility, responsive, assurance, and emphaty to depend on the particular satisfaction simultaneously. Emphaty dimension is variable which influences with full and has the biggest impact on customers satisfaction Circle K of Regatta Apartment Jakarta.